2005
DOI: 10.1002/gps.1286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of integrated emotion‐oriented care versus usual care on elderly persons with dementia in the nursing home and on nursing assistants: a randomized clinical trial

Abstract: Emotion-oriented care is more effective with regard to the emotional adaptation in nursing homes of persons with a mild to moderate dementia. For the severely demented elderly we did not find this surplus value. This outcome is of clinical importance for elderly persons with dementia who are cared for in nursing homes. With respect to the nursing assistants it is concluded that emotion-oriented care has a positive influence on stress reactions in some of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
160
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 19 publications
1
160
1
Order By: Relevance
“…This study shows that it is possible to detect which persons with dementia are at risk for a lower QOL across different QOL domains; therefore, it seems possible to target interventions to improve QOL. Interventions such as group cognitive stimulation therapy (GCST) [66], integrated emotion-oriented care [67], emotional adaptation [68], improving pain management [23] and research on the effect of organization of LTCF [69], and the effect of an outdoor space such as a garden [70], show promise with regard to the aim of improving QOL in persons with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that it is possible to detect which persons with dementia are at risk for a lower QOL across different QOL domains; therefore, it seems possible to target interventions to improve QOL. Interventions such as group cognitive stimulation therapy (GCST) [66], integrated emotion-oriented care [67], emotional adaptation [68], improving pain management [23] and research on the effect of organization of LTCF [69], and the effect of an outdoor space such as a garden [70], show promise with regard to the aim of improving QOL in persons with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…A large majority of participants in NPT studies were female, yet only 2 RCTs reported analyses according to the gender of the care receiver [42,109] . Some studies suggest that greater cognitive, functional and behavioral responses might be observed in less advanced dementia [231,232] , but these hypotheses were barely explored [212] .…”
Section: Key Findingsmentioning
confidence: 99%
“…Module 2: a skill development module, using interactive video-clips to practise observation and interviewing. This allowed staff to move away from the traditional 'antecedent-behaviour-consequence' observational approach to that of observing the relationship between emotion and communication through the behaviour, 93 in order to enhance emotion-orientated care 94 where relevant. The intention was to enable staff to appreciate the 'language of behaviour', 95 that is, the feelings and intentions of the person with dementia that were being communicated by the behaviour, using observation of real-life practice in the care setting and thus recognise triggers and early warning signs that can then be acted on to prevent escalation of the behaviour into full-blown CB.…”
Section: Introductionmentioning
confidence: 99%